Two-stage gradient-pore microporous layers for enhanced energy production and durability in PEM fuel cells - Saad S. Alrwashdeh (Center of Biomass & Renewable Energy (CBIORE), 2026)
Coupled mass, heat, and water transport in proton exchange membrane fuel cells (PEMFCs) critically depend on the microporous layer (MPL), but traditional uniform-pore MPLs are restricted by inherent trade-offs between the accessibility of reactants and the removal of liquid-water. This work presents a two-stage gradient-pore MPL structure and demonstrates its efficiency in terms of a fully coupled, non-isothermal Multiphysics modelling framework, the solution presented is theory-based and mitigates the classical trade-off between gas transport and liquid-water management by introducing a staged pore/porosity architecture that improves oxygen accessibility while promoting directional water evacuation. The proposed design uses a step-pore-size and porosity distribution throughout the MPL thickness to apply a directional capillary pressure gradient so that selective evacuation of water can occur to maintain catalyst-layer hydration. The optimized design is 12 to 18% more peak power density, 10 to 15% higher cell voltage (high current densities 1.5 A.cm-1 and higher), and 30% less cathode liquid saturation than a conventional MPL operating under the same conditions. Thermal analysis also shows that there was 25-35% decrease in temperature non-uniformity, which shows better homogeneity in current density and means that the hotspots causing degradation were caused to fail. Operating-regime mapping validates a strong transition between a transport-limited and optimal performance space, exhibiting increased robustness over a broad operating span. Such findings make pore-gradient engineering a physically based and scalable optimization strategy of improving energy production, thermal stability and durability of next-generation PEM fuel cells concurrently.